Levels and potential drivers of under‐five mortality sex ratios in low‐ and middle‐income countries. Issue 5 (26th May 2021) - Costa, Janaína Calu; Weber, Ann M.; Abdalla, Safa; Darmstadt, Gary L.; Victora, Cesar G.
Abstract: Background: Non‐biological childhood mortality sex ratios may reflect community sex preferences and gender discrimination in health care. Objective: We assessed the association between contextual factors and gender bias in under‐five mortality rates (U5MR) in low‐ and middle‐income countries. Methods: Full birth histories available from Demographic and Health Surveys and Multiple Indicator Cluster Surveys (2010‐2018) in 80 countries were used to estimate U5MR male‐to‐female sex ratios. Expected sex ratios and their residuals (difference of observed and expected) were derived from a linear regression model, adjusted for overall mortality. Negative residuals indicate more likelihood of discrimination against girls, and we refer to this as a measure of potential gender bias. Associations between residuals and national development and gender inequality indices and with survey‐derived child health care indicators were tested using Spearman's correlation. Results: Mortality residuals for under‐five mortality were not associated with national development, education, religion, or gender inequality indices. Negative residuals were more common in countries where boys were more likely to be taken to health services than girls (rho −0.24, 95% confidence interval −0.45, −0.01). Conclusions: Countries where girls were more likely to die than boys, accounting for overall mortality levels, were also countries where boys were more likely to receive health care than girls. Further research is needed to understand which national characteristics explain the presence of gender bias, given that the analyses of development levels and gender equality did not discriminate between countries with or without excess mortality of girls. Reporting on child mortality separately by sex is required to enable such advances.